Imagined Identities and Imagined Communities: Colombian English Teachers' Investment in Their Professional Development - Marcela Ovalle Quiroz; Adriana González (Universidad Nacional de Colombia, 2023)
English teachers' professional development responds to individual needs and societal discourses about teaching, learning, and language use. This paper reports the findings of a case study that explored the factors that increased or limited the active and committed participation of nine Colombian teachers of English in professional development programs. Findings suggest that English teachers are invested in their professional development if they may develop three imagined identities-as proficient English speakers, ELT experts, and ICT competent users-and their affiliation to an imagined community of "bilinguals." The teachers' journey to the imagined identities and the imagined community is full of conflicting emotions amidst the socio-political context of their work and the country's language education policies.